Analisis Sistem Manajemen Keamanan Informasi Menggunakan Sni Iso/Iec 27001:2013 Pada Pemerintahan Daerah Kota Sukabumi(Studi Kasus: Di Diskominfo Kota Sukabumi) - Winda Apriandari; Ashwin Sasongko (The Faculty of Science and Technology, 2018)
DISKOMINFO (Communication and Information Service ) of Sukabumi is a governmentinstitution that has responsibility for the management of Information and CommunicationTechnology in Local Government (PEMDA) Sukabumi. Sukabumi Information Technologymanaged by Head of Infrastructure of ICT, Encryption and Data Integration. From the results ofinterviews and observation , DISKOMINFO has problems on managing data securit, is becauselack of Human Resources, lack of awareness and responsibility and implementation of poorinformation security that cause incidents or hacking of information security, especially inSukabumi City Information System. this causes disruption of the process of public service andbusiness in DISKOMINFO.The Information Security Management System (ISMS) is a managementsystem implemented by organizations, especially governments organitations, to secure informationassets against threats that exist within the scope of DISKOMINFO. The process carried out usingthe PDCA cycle approach among the Plan Do Check Act. The ISMS handle infomation aspectssuch as confidentiality, integrity, and availability information.The ISMS analysis uses SNI ISO /IEC 27001: 2013 and SNI ISO / IEC 31000: 2009 risk management base. The ISMS analysispurpose to identify risk profiles by identifying assets, threats, and vulnerabilities as well asevaluating and controlling disruptions. ISMS produce security information manual, informationsecurity procedure, work instruction and information security form.